A Comprehensive Review on Third-Generation Photovoltaic Technologies - De, Arko; Bhattacharjee, Jyoti; Chowdhury, Sahana R.; Roy, Subhasis (Journal of Chemical Engineering Research Updates, 2023)
The renewable energy industry has revolutionized due to photovoltaic (PV) technologies, which offer a clean and sustainable alternative to conventional energy sources. Third-generation photovoltaic technologies refer to a group of emerging PV technologies aiming to surpass the efficiency and cost-effectiveness of traditional silicon-based solar cells. Different ceramic materials have also been investigated for use in these advanced PV technologies. This review examines the science, current state, and advancements of third-generation PV systems for wide-scale implementation. The first section of this study provides an overview of the development of PV technologies from the first to the third generation, highlighting the most significant novel developments made at each step. Organic photovoltaic (OPV) cells, dye-sensitized solar cells (DSSCs), and perovskite solar cells (PSCs) are discussed here as a few new technologies that constitute the third generation, also known as the next generation of advanced PV. This review presents how these devices can be used in specialized settings, including indoor and low-light environments, thereby expanding the range of energy harvesting potential. The brief history of these emerging technologies, their current status, future developments, and key challenges are discussed in this review paper.